Analysis of Evidence Seizure in Money Laundering Crimes: Procedures, Legitimacy, and Its Impact on Legal Proceedings - Phireri, Phireri; Dwiyanti, Asti (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, the seizure of evidence in Money Laundering Crimes (TPPU) should be conducted in accordance with applicable laws and regulations to ensure the validity of evidence that can be used in legal proceedings. In reality, numerous issues arise regarding the regulation and procedures for evidence seizure, which often impact the validity of the evidence. This study aims to analyze the regulations and procedures for evidence seizure in TPPU cases and their implications for the validity of evidence in legal processes. This article is categorized as library research using a qualitative approach. The methodology employed is normative juridical analysis. The findings reveal that evidence seizure in TPPU cases is often not conducted in accordance with established procedures, thereby potentially undermining the validity of the evidence. The money laundering process, which consists of the placement, layering, and integration stages, frequently involves suspicious transactions that require stricter supervision.